ANALISIS KINERJA KEUANGAN KOPERASI PADA KOPERASI SERBA USAHA (KSU) REJOSARI KELURAHAN REJOSARI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Warda, Novida; ', Caska; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: The research aims to identify and analyze the financial performance of Co-operative Serba Usaha (KSU) Rejosari Pekanbaru city views from its financial ratios 2011-2015. Where the research was conducted in the environment Co-operative Serba Usaha (KSU) Rejosari in Pekanbaru. Research of the month August 2016 to March 2017. The type of research is quantitative descriptive, which describes the results of research in the form of financial reporting data related to the financial performance of the co-operative. Source of research data is the data obtained from the Co-operative Serba Usaha (KSU) Rejosari Management Accountability Reports Pekanbaru City years from 2011-2015. The data collection techniques used is the method of documentation. The results showed that the financial performance of Pekanbaru City Cooperative of the years 2011-2015 showed good results. This is because the conditions Liquidity Ratio (Current Ratio), Solvency Ratio (Debt to Equity Ratio and Debt to Total Assets), Ratios Profitability (Return on Equity, Return on Assets and Net Profit Margin) and Activity Ratios (Asset Tours Over, Recaivable Turn Over and Co-operative Business Transactions with Members Cooperative). Most of the financial performance of cooperatives have a very good performance, and there are some ratio performance is quite good and not good. Thus it can be said that the Co-operative Serba Usaha (KSU) Rejosari of Pekanbaru included in the category of good.Keywords : Monetary Performance, Ratio of Likuiditas, Solvency Ratio, RatioProtability and ActivityRatio.